VIDEO PRESENTASI, BLENDED LEARNING, COGNITIVE LOAD DAN HASIL BELAJAR: SUATU KAJIAN TEORITIS - Intan Safiah; Muhammad Yunus (Jurnal Pesona Dasar, 2020)
Video Presentation is a learning medium that is very supportive of the e-learning-based learning process. Learning videos can help reduce the cognitive load of learners. Cognitive load is a theoretical concept with a very central role in the educational research literature. The basic idea of cognitive load theory is that cognitive capacity in working memory is limited, so that if the learning task requires too much capacity, learning will be hampered. This study aims to review the results of research that explores the use of video presentations to overcome cognitive load in blended learning. Through a review of research on learning using a published video presentation model. The aim of this study is to identify strategies used by researchers in overcoming cognitive load in learning activities, and also to synthesize current literature on the impact of using video presentations on learning outcomes. This study uses a research library research method. The results of the study found that one way to optimize the use of working memory capacity and avoid cognitive overload is to design an instructional system, one of which is a video presentation. Cognitive load theory has been researched and proven to be overcome by using video presentations. This study openly explores the limitations of video presentations in blended learning to overcome cognitive load and improve learning outcomes by identifying a number of related conceptual, methodological and application problems.